Communication of Time in Africa - Nnajiofor, Osita (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
I showed in this paper that time is communicated in traditional Africa Sub–Saharan Africa through proverbs, songs, riddles, fables, poems, etc. but in contemporary African society, a lot of transformation has occurred with the introduction of modern apparatus like watches, clocks and other social media outlets. The introduction of these contemporary devices led to the total abandonment of traditional African unique ways of communicating time. The mindless abandonment has created a lot of generational vacuum in the mind of many contemporary African children who are ignorant of this method. If not addressed, this ignorance will lead to the total extinction of African cherished values. I conclude this paper by maintaining that although African traditional communication of time should be maintained, it is germane to complement it with contemporary time devices. I used the analytic method of philosophy to arrive at the conclusion